Heterogenous Factors of Adoption of Agricultural Technologies in West and East Africa Countries: A Review - Oyetunde-Usman, Zainab (Frontiers in Sustainable Food Systems, 2022)
This review brings to light, extensive body of research on the evolvement of agricultural technology in Sub-Saharan Africa with focus on adoption studies in West and East Africa countries. The review highlights historical green revolution events and the heterogeneity in the determinants of the adoption of agricultural technology. Three key popular indicators in adoption studies were reviewed for their heterogeneity; this includes land, extension & social institutions, and gender in light of comparison of studies in West and East Africa. The review shows that there is so much to be gained from enhancing the understanding of the heterogeneity that exists in key popular indicators in adoption studies considering the importance of adoption of agricultural technology in reducing poverty and food insecurity and the evolving impact of climate change and other human attributes that has defined the modification of various agricultural technology. Also, the review highlights the need to tailor extension and social learning toward existing heterogeneity to aid in promoting the adoption of agricultural technology. An important highlight includes the need to be wary of the downsides of the earlier green revolution while driving the efforts of new green revolution in West and East Africa and Sub-Saharan Africa in general.